Studies of Sexuality in Archaeology: theoretical and methodological approaches from a sociological interpretation - Álvarez Chávez, Roland (2018)
With the present paper I tried to open and initiate a site for the reflection and the debate around the studies of sexuality in the prehispanic period, from a sociological approach and using archaeological evidence, considering that both disciplines have not coincided in the work of interpreting the material evidence on the subject so far. This paper considers an approach that focuses its analysis on the hypothesis that the subjects of past societies have had diverse sexual expressions and practices, decentralized from a fixed identityconstruction and under a richer and more fluid sexuality practices.